Small‐Molecule‐Mediated Axonal Branching in Caenorhabditis elegans. Issue 3 (29th January 2013) - Zlotkowski, Katherine; Pierce‐Shimomura, Jon; Siegel, Dionicio
<x xml:space="preserve">Abstract</x> An in vivo system for monitoring small‐molecule‐mediated neuronal branching has been developed by using C. elegans. Growth‐promoting compounds can be detected by visual inspection of GFPlabeled cholinergic neurons, as axonal branching occurs following treatment with neurotrophic agents. Investigation of the structure–activity relationship of the neurotrophic natural product clovanemagnolol (1) led us to a comparable chemically edited derivative.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>